A new U–Pb zircon age for an ash layer at the Bathonian–Callovian boundary, Argentina - Kamo, Sandra L. (2009)
A U–Pb zircon age of 164.64^0.2 Ma (95% confidence level) is reported for an ash bed, at the Bathonian–Callovian (late Middle Jurassic) boundary, determined by isotope dilution thermal ionisation mass spectrometry from individual, chemically abraded grains. The volcanic ash layer occurs within the Chacay Melehue Formation, Chacay Melehue section, Neuque´n Province, central west Argentina, above the last record of ammonites of the regional Lilloettia steinmanni Standard Zone, and, stratigraphically, where the first of those of the regional Eurycephalites vergarensis Standard Zone appears, generally referred to as the uppermost Bathonian and the lowermost Callovian, respectively. This ash layer represents the only known datable horizon worldwide that is directly related to a well-documented ammonite faunal succession at this boundary. The U–Pb zircon age is older than one previously reported for the same bed and closer to an estimation of 164.7^4Ma for the boundary based on the scaling durations of ammonite zones to their subzones in the sub-boreal standard zonation. The new age agrees better with the age model for the Oxfordian through Bathonian M-sequence magnetic anomalies in the Pacific and contributes to the radioisotopic age calibration of the Jurassic time scale.